The coagulant type influence on removal efficiency of 5- and 6-ring PAHs during water coagulation process = Wpływ rodzaju koagulantu na skuteczność usuwania 5- i 6- pierścieniowych WWA z wody w procesie koagulacji - Nowacka, Anna; Włodarczyk-Makuła, Maria (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The article presents results on investigation of the removal efficiency of selected 5- and 6-ring polycyclic aromatic hydrocarbons (benzo[a]pyrene, benzo[b]fluoranthene, benzo[k]fluoranthene, benzo[j]fluoranthene, benzo[g,h,i]perylene, indeno[1,2,3-cd]pyrene, dibenzo[a,h]anthracene) from water during coagulation and sedimentation process. Two pre-hydrolyzed aluminum coagulants: PAX XL 19H and FLOKOR 105V were chosen for research.
Keywords: koagulacja; usuwanie WWA; koagulanty wstępnie zhydrolizowane; uzdatnianie wody; coagulation; removal of PAHs; pre-hydrolyzed coagulants; water treatment